Consort Yu - Yao Hsiao (Journal of the Association for Technology in Music Instruction, 2025)
In Consort Yu for voice and live electronics, the integration of hand gestures and the use of Leap Motion holds profound significance in presenting Peking Opera. Unlike modern acting conventions, Peking Opera performers rely heavily on hand gestures to convey emotion and narrative. With limited body movements, gestures such as the iconic "Lotus Finger" become essential tools for expression. These nuanced gestures convey a wide range of emotions and intentions, enriching the storytelling experience. My creative process bridges the rich traditions of Peking Opera with the realm of contemporary electronic music. First, I imitated the timbres and rhythms characteristic of The Hegemon-King Bids His Lady Farewell. The use of unstable pulses, such as tempo rubato and voice glissando—hallmarks of Peking Opera—resonates within the vibrant palette of contemporary music. Additionally, I incorporated traditional Peking Opera singing styles and selectively adapted melodic motifs from the original opera, imbuing them with novel harmonic nuances. Central to my exploration was the innovative incorporation of technology, particularly the Leap Motion device, into the performance framework. My approach extends beyond mere utilization; I transformed this utilitarian device into a musical instrument, enriching the sonic and gestural landscape of the composition. Through meticulous choreography informed by both the technological capabilities of Leap Motion and the artistic intentions derived from Peking Opera, I achieved a seamless fusion of artistry and innovation. I strategically employed both triggers and continuous controls to imbue the performance with expressive depth and nuance. By highlighting the symbiotic relationship between choreography, technology, and musical expression, I invited audiences from diverse backgrounds to engage with the creative process, fostering a deeper appreciation of the interplay between science and artistry in live electronic performance. In the live rendition of Consort Yu, the Leap Motion device becomes an extension of the performer’s artistic vision, facilitating real-time manipulation of electronic elements while seamlessly integrating with traditional vocal delivery. This symbiosis of tradition and innovation epitomizes the spirit of NIME, showcasing the transformative potential of technology in the service of musical expression. My contribution lies not only in the use of technology but also in the innovative and musical integration of triggers and continuous controls through the Leap Motion device, enriching the understanding of my creative process within both scientific and artistic communities.
Keywords: composition